Publication bias in systematic reviews - Barbui, Corrado; Cipriani, Andrea (Archives of General Psychiatry, 2007)
Comments on an article by M. J. Taylor et al. (see record [rid]2006-21397-007[/rid]). The author suggested that selective serotonin reuptake inhibitors (SSRIs) begin to have observable beneficial effects in depression during the first week of treatment. This result was obtained from the analysis of randomized controlled trials of SSRIs vs placebo that reported outcomes for at least 2 points in the first 4 weeks of treatment. We argue that the criteria of including only studies reporting outcomes for at least 2 points in the first 4 weeks of treatment might have systematically selected positive trials, that is trials showing significant differences between placebo and active drugs during the early phases of the trial. Systematic reviews should routinely include details not reported in scientific journals and data from trials that have never been published; additionally, systematic reviews should increasingly include reanalyzes of individual patient data. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: Antidepressant Drugs; Depressive Disorder; Drug Industry; Drug Therapy; Humans; Major Depression; Periodicals as Topic; Placebos; Publication Bias; Publishing; Randomized Controlled Trials as Topic; Research Support as Topic; Review Literature as Topic; Serotonin Reuptake Inhibitors; Serotonin Uptake Inhibitors; Treatment Outcome; antidepressant action; depression; early onset; selective serotonin reuptake inhibitor